2014
DOI: 10.1021/am506365a
|View full text |Cite
|
Sign up to set email alerts
|

Precise Identification and Manipulation of Adsorption Geometry of Donor−π–Acceptor Dye on Nanocrystalline TiO2 Films for Improved Photovoltaics

Abstract: Adsorption geometry of dye molecules on nanocrystalline TiO2 plays a central role in dye-sensitized solar cells, enabling effective sunlight absorption, fast electron injection, optimized interface band offsets, and stable photovoltaic performance. However, precise determination of dye binding geometry and proportion has been challenging due to complexity and sensitivity at interfaces. Here employing combined vibrational spectrometry and density functional calculations, we identify typical adsorption configura… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
37
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(48 citation statements)
references
References 63 publications
9
37
2
Order By: Relevance
“…To understand the effect of cyano group on the stability of adsorption, we compared both A and B series and found that, the substitution of cyano group has no significant influence on adsorption energy in the configurations which is not directly bound to the surface (B1-B3). Whereas it increases in B4 and B5 configurations because of its direct binding to the surface and among the considered adsorption configurations, B5 is the most stable one due to the strong hydrogen bonding along with two covalent bonds (O-Ti and N-Ti) with the surface, which is in agreement with the previous studies 41, 50 . The calculated bond lengths are r O-Ti  = 2.025 Å, r N-Ti  = 2.264 Å and r H-O2c  = 1.062 Å (See Table 1).…”
Section: Resultssupporting
confidence: 91%
“…To understand the effect of cyano group on the stability of adsorption, we compared both A and B series and found that, the substitution of cyano group has no significant influence on adsorption energy in the configurations which is not directly bound to the surface (B1-B3). Whereas it increases in B4 and B5 configurations because of its direct binding to the surface and among the considered adsorption configurations, B5 is the most stable one due to the strong hydrogen bonding along with two covalent bonds (O-Ti and N-Ti) with the surface, which is in agreement with the previous studies 41, 50 . The calculated bond lengths are r O-Ti  = 2.025 Å, r N-Ti  = 2.264 Å and r H-O2c  = 1.062 Å (See Table 1).…”
Section: Resultssupporting
confidence: 91%
“…The reduction energy in this DFT comparison of adsorption modes is also consistent with the red shifting observed in the associated UV/vis absorption spectroscopy results mentioned above. Our DFT results are also corroborated by related computational work 38. The optimised geometry of the MK-44 dye•••TiO2 interfacial structure in the presence of Li + was then calculated, assuming that isomeric geometry is maintained upon addition of this cation 60.…”
supporting
confidence: 80%
“…Figure 1 Molecular structures and preferred TiO2 binding modes of; a) MK-2; and b) MK-44. 37,38 Annotated lateral molecular lengths and widths are taken from their crystal structures which were derived from X-ray diffraction data. 39 Since neutrons are able to detect hydrogen atoms much better than X-rays, additional values (in parentheses) for these lateral dimensions are presented which incorporates the explicit position and bond lengths of hydrogen atoms, whose presence may be discounted during XRR studies.…”
mentioning
confidence: 99%
“…Efficient attachment can be obtained by the incorporation of suitable anchoring groups capable of connecting to the semiconductor's surface. Among others, aminoacid, anhydride, carboxylate,, cyanoacrylate,, ester,, hydroxamate,, pyridyl, and phosphonate groups have been used for that purpose. It is also possible to introduce a linkage molecule that is able to interact with both the chromophore and the semiconductor surface.…”
Section: Introductionmentioning
confidence: 99%